Cell wall proteomics of sugarcane cell suspension cultures. Issue 6 (6th March 2014) - Calderan‐Rodrigues, Maria Juliana; Jamet, Elisabeth; Bonassi, Maria Beatriz Calderan Rodrigues; Guidetti‐Gonzalez, Simone; Begossi, Amanda Carmanhanis; Setem, Laís Vaz; Franceschini, Livia Maria; Fonseca, Juliana Guimarães; Labate, Carlos Alberto
Abstract : The use of cell walls to produce cellulosic ethanol from sugarcane bagasse is a new challenge. A better knowledge of proteins involved in cell wall remodelling is essential to improve the saccharification processes. Cell suspension cultures were used for this first cell wall proteomics study of sugarcane. Proteins extracted from cell walls were identified using an adapted protocol. They were extracted using 0.2 M CaCl2 and 2 M LiCl after purification of cell walls. The proteins were then identified by the innovative nanoACQUITY UPLC MS/MS technology and bioinformatics using the translated SUCEST EST cluster database of sugarcane. The experiments were reproduced three times. Since Sorghum bicolor is the closest plant with a fully sequenced genome, homologous proteins were searched for to complete the annotation of proteins, that is, prediction of subcellular localization and functional domains. Altogether, 69 different proteins predicted to be secreted were identified among 377 proteins. The reproducibility of the experiments is discussed. These proteins were distributed into eight functional classes. Oxidoreductases such as peroxidases were well represented, whereas glycoside hydrolases were scarce. This work provides information about the proteins that could be manipulated through genetic transformation, to increase second‐generation ethanol production.